Physical Process Contributions to the Development of a Super Explosive Cyclone Over the Gulf Stream - Zhang, Shuqin; Liu, Chunlei; Xu, Jianjun; Zhang, Shaojing; Tang, Ruoying; Huang, Zhefan; Zheng, Yanzhu; Guan, Zhuoqiang; Mao, Hongfei; Xue, Yufeng (Frontiers in Earth Science, 2021)
Contributions of different physical processes to the development of a super explosive cyclone (SEC) migrating over the Gulf Stream with the maximum deepening rate of 3.45 Bergeron were investigated using the ERA5 atmospheric reanalysis from European Centre for Medium-Range Weather Forecasts (ECMWF). The evolution of the SEC resembled the Shapiro-Keyser model. The moisture transported to the bent-back front by easterlies from Gulf Stream favored precipitation and enhanced the latent heat release. The bent-back front and warm front were dominated by the water vapor convergence in the mid-low troposphere, the cyclonic-vorticity advection in the mid-upper troposphere and the divergence in the upper troposphere. These factors favored the rapid development of the SEC, but their contributions showed significant differences during the explosive-developing stage. The diagnostic results based on the Zwack-Okossi equation suggested that the early explosive development of the SEC was mainly forced by the diabatic heating in the mid-low troposphere. From the early explosive-developing moment to maximum-deepening-rate moment, the diabatic heating, warm-air advection and cyclonic-vorticity advection were all enhanced significantly, their combination forced the most explosive development, and the diabatic heating had the biggest contribution, followed by the warm-air advection and cyclonic-vorticity advection, which is different from the previous studies of ECs over the Northwestern Atlantic. The cross section of these factors suggested that during the rapid development, the cyclonic-vorticity advection was distributed and enhanced significantly in the mid-low troposphere, the warm-air advection was strengthened significantly in the mid-low and upper troposphere, and the diabatic heating was distributed in the middle troposphere.